(untitled) (Nepal Journal of Epidemiology, 2014)
Abstracts of the Oral Presentations at the session on Health Economics and climate change at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10178